Variability in surgical techniques for cochlear implantation: an international survey study. (4th July 2022) - Kant, Ellen; Markodimitraki, Laura M.; Stegeman, Inge; Thomeer, Hans G. X. M.
Abstract : Objective: This study aimed to gain insight into current practices regarding the surgical techniques used for positioning and fixation of internal components of the cochlear implant. Methods: A questionnaire focused on surgical techniques used for cochlear implantation was distributed among 441 cochlear implant surgeons. Descriptive statistics were reported. Results: The questionnaire was completed by 59 surgeons working in 13 different countries. The most preferred incision shapes were the S-shape (41%) and the C-shape (36%). The preferred implantation angle for the receiver/stimulator device was either 45° (64%) or 60° (30%), relative to the Frankfurter Horizontal Plane. Most respondents used a drilled bony well with (42%) or without a subperiosteal pocket (31%) to fixate the receiver/stimulator device. All respondents used the facial recess approach. Most used the round window insertion technique to enter the scala tympani (73%). Approximately half of the respondents preferred the lateral wall electrode array, whereas the other half preferred the perimodiolar electrode array. During their career, most (86%) changed their technique towards structure preservation and minimizing trauma. Conclusion: This study indicates variability in the surgical techniques used to position and fixate the internal components of the cochlear implant. Additionally, surgical preference transits towards structure preservation and minimal invasiveness.